Overview of Kampung SAGU in Improving Knowledge and Self-Management of Diabetic Patients in Pakuan Baru Community Health Center - Raodah; Chandra Pranata Salim; Assyifa Qalbiyah; Annisa Susanne Sarjono; Dhea Olivia Az Zahra (Sumatera Medical Journal, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels. Indonesia ranks seventh in global diabetes prevalence, with approximately 10.7 million individuals affected. Community Health Center, as a primary healthcare provider, emphasizes promotive and preventive efforts to implement the 5 Pillars of DM. Kampung Sadar Gula (SAGU) is a program run by the Pakuan Baru Community Health Center that provides education, health examinations, and routine medication to improve the quality of life of people with DM within the community. Objective: to determine the impact of Kampung SAGU program in improving the knowledge and self-management of DM patients in Pakuan Baru Community Health Center in Jambi City. Methods: Descriptive research was conducted using purposive sampling and research instruments such as questionnaires and interviews with program implementers. Results: most of the population demonstrated good knowledge of DM (54.5%). However, a significant portion of respondents still showed low levels of self-care (45.4%), physical activity (54.5%), and medication adherence (45.4%). Conclusion: the level of achievement in independent eating, physical activity, and medication compliance is still low among the community of Kampung SAGU. Therefore, further monthly education for patients with uncontrolled blood sugar levels and their families is recommended.